Variation in Equilibrium Temperature, Mixed Layer Depth, and Boundary Layer Cloud Over Land in a Doubled CO\(_2\) Climate: An Idealized Model Approach - Betts , Alan K.; Chiu, J. Christine (Emerging Issues in Environment, Geography and Earth Science Vol. 4, 2023)
An idealized equilibrium model for the undisturbed partly cloudy boundary layer (BL) is used as a framework to explore the coupling between the surface, the energy, water, and carbon cycles over land in midlatitudes, and show the sensitivity to the clear-sky shortwave flux, the midtropospheric temperature, moisture, CO2, and subsidence. The changes in the surface fluxes, the BL equilibrium, and cloud cover are shown for a warmer, doubled CO2 climate. Reduced stomatal conductance in a simple vegetation model amplifies the background 2 K ocean temperature rise to an (unrealistically large) 6 K increase in near-surface temperature over land, with a corresponding drop of near-surface relative humidity of about 19%, and a rise of cloud base of about 70 hPa. Sensitivity studies give insight into how clear-sky and cloud radiative feedbacks and a vegetated land surface interact to give different solutions for equilibrium temperature, and how they respond to doubled CO2, Cloud changes depend strongly on changes of mean subsidence; but evaporative fraction (EF) decreases. EF is almost uniquely related to mixed layer (ML) depth, independent of background forcing climate. This suggests that it might be possible to infer EF for heterogeneous landscapes from ML depth. The asymmetry of increased evaporation over the oceans and reduced transpiration over land increases in a warmer doubled CO2 climate.